Transcription of Simian Virus 40 II. Hybridization of RNA Extracted from Different Lines of Transformed Cells to the Separated Strands of Simian Virus 40 DNA - Ozanne, Brad (1973)
The amount of simian virus 40 (SV40) DNA present in various SV40-transformed mouse cell lines and “revertants” isolated from them was determined. The number of viral DNA copies in the different cell lines ranged from 1.35 to 8.75 copies per diploid quantity of mouse cell DNA and from 2.2 to 14 copies per cell. The revertants had the same number of viral DNA copies per diploid quantity of mouse cell DNA as their parental cell lines. (However, they showed an increased number of viral DNA copies per cell due to their increased amount of DNA.) By using separated strands of SV40 DNA, the extent of each DNA strand transcribed into stable RNA species was determined for the transformed and “revertant” cell lines. From 30 to 80% of the “early” strand and from 0 to 20% of the “late” strand was present as stable RNA species in the cell lines tested. There was no alteration in the pattern of the stable viral RNA species present in three concanavalin A-selected revertants, whereas in a fluorodeoxyuridine-selected revertant there appeared to be less viral-specific RNA present in the cells.